Nasal glioma. - Lastilla, G.; Valentini, D.; Bonifazi, E.; Ingravallo, G. (European Journal of Pediatric Dermatology, 2006)
A 35-day-old baby presented since birth a nodule of the right nasopalpebral region. The nodule, which had not further grew, was not modified by crying. On physical examination, there was a 1.5 cm in size nodule, covered by normal skin, hard-elastic, with sharp outline and fixed to the deep layers. MRI ruled out the existence of fistulas and the communication with meningeal encephalic or endonasal structures. The child underwent surgical operation at the age of 5 months. The histological examination of the nodule showed a dermohypodermic proliferation consisting of isles of mature neuroglial tissue, surrounded by bundles of fibrous connective tissue. These findings led to diagnose cerebral heterotopy of the nose (nasal glioma), extranasal form. At the age of 6, the child is healthy with a residual nasal scar.